(untitled) (Papeles, 2025)
Introduction: The Mexican Dual Training Model (MMFD) is a type of training for work, where the student receives academic instruction at high school and job training in the company. The article examines the factors that influence the functioning of the MMFD and if the theory-practice link occurs in it, as well as the development of professional skills. The theorical framework is support on the categories of codified knowledge, employability and critical factors. Methodology: To collect information the article uses a qualitative perspective, with the application in depth interviews and focus groups with business trainers, human resources managers, school linkers, academic tutors and dual students. Results and discussion: In dual training there is a coherent articulation between theory and practice with effects on the acquisition of technical and soft skills, which increases the opportunities for graduates to enter into quality jobs. The elements that determine this configuration are found in the activities that connect the productive and school spheres: the selection and support of students, the knowledge of the program by teachers and workers, the assignment of activities to the actors involved and the relationship with the families. Conclusions: The functionating of the MMFD is based on coordination between the school linker and the business trainer. The relationship between these actors influences the compliance with the study program, the correspondence grid, the rotation plan and attention to critical factors.